1986
DOI: 10.1002/j.1460-2075.1986.tb04256.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of superoxide dismutase mutants in Escherichia coli: is superoxide dismutase necessary for aerobic life?

Abstract: Mu transposons carrying the chloramphenicol resistance marker have been inserted into the cloned Escherichia coli genes sodA and sodB coding for manganese superoxide dismutase (MnSOD) and iron superoxide dismutase (FeSOD) respectively, creating mutations and gene fusions. The mutated sodA or sodB genes were introduced into the bacterial chromosome by allelic exchange. The resulting mutants were shown to lack the corresponding SOD by activity measurements and immunoblot analysis. Aerobically, in rich medium, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
481
2
5

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(505 citation statements)
references
References 37 publications
17
481
2
5
Order By: Relevance
“…H 2 O 2 can diffuse rapidly through cell membranes. A higher sensitivity of SOD mutants to exogenous H 2 O 2 has been reported (Carlioz & Touati, 1986;Poyart et al, 2001). Since only insignificant differences in growth characteristics were observed between the wild-type and the DsodA mutant, it may be concluded that the quantity of ROS produced by Ent.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…H 2 O 2 can diffuse rapidly through cell membranes. A higher sensitivity of SOD mutants to exogenous H 2 O 2 has been reported (Carlioz & Touati, 1986;Poyart et al, 2001). Since only insignificant differences in growth characteristics were observed between the wild-type and the DsodA mutant, it may be concluded that the quantity of ROS produced by Ent.…”
Section: Discussionmentioning
confidence: 68%
“…O N{ 2 is a powerful oxidant that reacts with biomolecules, including DNA, at virtually diffusion-limited rates. Thus, the higher free iron levels in SOD mutants also explain why they are more sensitive to killing by H 2 O 2 than their wild-type counterparts (Carlioz & Touati, 1986). This effect of H 2 O 2 can be blocked by cellpermeable iron chelators, confirming that the killing is mediated by Fenton chemistry (Imlay & Linn, 1988).…”
Section: Reactive Oxygen Species (Ros) Including Superoxide Anion (O N{mentioning
confidence: 90%
“…Samples of the culture were harvested at different times during growth, and the cells were suspended in potassium phosphate buffer (100 mM; pH 7.0). They were disrupted by five cycles of freezing and thawing (dry ice-42ЊC) (10). Protein concentrations were determined by the method of Bradford (7) with the Bio-Rad protein assay (6), using bovine serum albumin (BSA) as standard.…”
Section: Methodsmentioning
confidence: 99%
“…This deficiency may arise from the oxidation of the dihydroxyethyl thiamine intermediate of transketolase (26), but firm structural evidence is lacking. SOD mutants of both E. coli and S. cerevisiae are also unable to perform normal sulfur metabolism (12,27); in this case the causal lesion remains completely unknown. It is likely that additional injuries remain to be identified.…”
Section: What Biomolecules Do Superoxide and H 2 O 2 Damage?mentioning
confidence: 99%